Model Pengelolaan Kurikulum Pendidikan Raudlatul Athfal (RA) Nurul Iman Kecamatan Leuwimunding Kabupaten Majalengka - Mumu Muzayyin Maq (PT FORMOSA CENDEKIA GLOBAL, 2022)
Curriculum management in the context of improving the quality of education is very necessary and becomes the main orientation of an educational institution. The pattern in the implementation of curriculum management is the core of curriculum management. Curriculum management aims at curriculum development by focusing the foundation for intelligence, knowledge, personality, noble character, and skills to live independently to attend further education. The aims of this study were 1) to determine the management of the education curriculum of Raudlatul Athfal (RA) of Nurul Iman in Leuwimunding, Majalengka – West Java. 2) to describe the curriculum management model of Raudlatul Athfal (RA) of Nurul Iman in Leuwimunding sub-district, Majalengka district. This study used qualitative research methods. One of the procedures of this research is to produce descriptive data. The approach used in this study is a qualitative approach. This approach is carried out by conducting an in-depth exploration of the program, event, process, activity of one or more people. Data collection techniques used are observation and interview techniques. Data analysis was carried out by means of data reduction, data presentation, and drawing conclusions. The subjects used were 20 teachers and 1 (one) head and 2 (two) education staff (administration) at Raudlatul Athfal (RA) of Nurul Iman. Based on the results of the study, it was found that there were 5 (five) scopes in curriculum management, namely first, the preparation of programs for curriculum planning. Second, the preparation of the educational calendar. Third, the preparation of a schedule of activities. Fourth, the preparation of the learning activity schedule. Fifth, planning teaching and learning activities.